Nitrergic pathways and L-type calcium channel of MnPO influencing cardiovascular homeostasis - Saad, Wilson Abrão [UNESP]; Guarda, Ismael Francisco Motta Siqueira; Camargo, Luiz Antonio de Arruda [UNESP]; Santos, Talmir Augusto Faria Brizola dos; Simões, Sylvio; Saad, William Abrão (Science Alert, 2006)
The median preoptic nucleus (MnPO) is one of most important site of the lamina terminalis implicated in the regulation of hydro electrolytic and cardiovascular balance. The purpose of this study was to determine the effect of L-Type calcium channel antagonist, nifedipine, on the increase of median arterial blood pressure (MAP) induce by angiotensin II (ANG II) injected into the MnPO. The influence of nitric oxide (NO) on nifedipine antipressor action has also been studied by utilizing N W-nitro-L-arginine methyl ester (L-NAME) (40 μg 0.2 μL -1) a NO synthase inhibitor (NOSI), 7-nitroindazole (7-NIT) (40 μg 0.2 μL -1), a specific neuronal NO synthase inhibitor (nNOSI) and sodium nitroprusside (SNP) (20 μg 0.2 μL -1) a NO donor agent. We have also investigated the central role of losartan and PD123349 (20 nmol 0.2 μL -1), AT 1 and AT 2, respectively (selective non peptide ANG II receptor antagonists), in the pressor effect of ANG II (25 pmol 0.2 μL -1) injected into the MnPO. Male Wistar rats weighting 200-250 g, with cannulae implanted into the MnPO were utilized. Losartan injected into the MnPO, prior to ANG II, blocked the pressor effect of ANGII. PD 123319 only decreased the pressor effect of ANG II. Rats pre-treated with either 50 μg 0.2 μL -1 or 100 μg 0.2 μL -1 of nifedipine, followed by 25 pmol 0.2 μL -1 of ANG II, decreased ANG II-pressor effect. L-NAME potentiated the pressor effect of ANG II. 7-NIT injected prior to ANG II into the MnPO also potentiated the pressor effect of ANGII but with less intensity than that of L-NAME. SNP injected prior to ANG II blocked the pressor effect of ANG II. The potentiation action of L-NAME and 7-NIT on ANG II-pressor effect was blocked by prior injection of nifedipine. The results described in this study provide evidence that calcium channels play important roles in central ANG II-induced pressor effect. The structures containing NO in the brain, such as MnPO, include both endothelial and neuronal cells, which might be responsible for the influence of nifedipine on the pressor effect of ANG II. These data have shown the functional relationship between L-Type calcium channel and a free radical gas NO in the MnPO, on the control of ANG II-induced pressor effect acting in AT 1 and AT 2 receptors.
Keywords: Angiotensin II; Blood pressure; Calcium channel; MnPO; Nitric oxide; Rats; 1 (4 dimethylamino 3 methylbenzyl) 5 diphenylacetyl 4,5,6,7 tetrahydro 1h imidazo[4,5 c]pyridine 6 carboxylic acid; 7 nitroindazole; angiotensin; angiotensin 1 receptor; angiotensin 2 receptor; angiotensin 2 receptor antagonist; angiotensin I; calcium channel L type; losartan; n(g) nitroarginine methyl ester; nifedipine; nitric oxide; nitroprusside sodium; animal experiment; blood pressure measurement; cardiovascular function; controlled study; dose response; drug effect; endothelium cell; homeostasis; male; mean arterial pressure; nerve cell; nitrergic nerve; nonhuman; preoptic nucleus; pressor response; rat